2023
DOI: 10.24820/ark.5550190.p011.896
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of potential antiviral compounds through 1,3-dipolar cycloadditions. Part 2: nitrones, nitrile oxides and imines, and other 1,3-dipoles

Abstract: Prominent in the current stage of drug development, antiviral compounds can be efficiently prepared through cycloaddition reactions. This review reports the use of 1,3-dipolar cycloadditions of nitrones, nitrile oxides and imines and other 1,3-dipoles in the light of their application for the preparation of synthons in the design and synthesis of compounds that were tested for their antiviral activities against a variety of viruses. Since nitrile oxides represent valuable precursors of nitrosocarbonyl intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Prominent in the current stage of drug development, antiviral compounds can be efficiently prepared through cycloaddition reactions. In recent reviews we reported the use of 1,3-dipolar cycloaddition reactions of selected 1,3-dipoles, from azides 25 to nitrones, passing through nitrile oxides and other ylides, 26 in the light of their application for the preparation of key intermediates in the design and synthesis of compounds that were tested for their antiviral activities against a variety of viruses. The products obtained from these pericyclic reaction approaches were tested for their activities in terms of blocking the virus replication, and the relevant biological data are highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…Prominent in the current stage of drug development, antiviral compounds can be efficiently prepared through cycloaddition reactions. In recent reviews we reported the use of 1,3-dipolar cycloaddition reactions of selected 1,3-dipoles, from azides 25 to nitrones, passing through nitrile oxides and other ylides, 26 in the light of their application for the preparation of key intermediates in the design and synthesis of compounds that were tested for their antiviral activities against a variety of viruses. The products obtained from these pericyclic reaction approaches were tested for their activities in terms of blocking the virus replication, and the relevant biological data are highlighted.…”
Section: Discussionmentioning
confidence: 99%